PSYCHOLOGICAL AND PEDAGOGICAL FOUNDATIONS OF BUSINESS COMMUNICATION AMONG PARTICIPANTS IN THE DISTANCE LEARNING PROCESS - Pyshchyk , Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article analyzes the psychological and pedagogical foundations of business communication among participants in the distance learning process. It identifies key factors of effective communication in the digital environment, including emotional intelligence, pedagogical ethics, communicative culture, and digital competence. Based on the results of empirical research, a practical communication support model – the «4R» model – is proposed, which encompasses regularity, richness, reflection, and collaboration. The effectiveness of this model’s implementation in Ukrainian educational institutions has been proven as a means of enhancing student engagement, motivation, and the quality of interaction in distance learning.